Analysis of the Influence of Digital Marketing, Price, Product Quality on Purchasing Decisions of Batik Arkanza Consumers - Fathdila Fethikasari; Juni Kristanto (Escalate : Economics and Business Journal, 2026)
This study analyzes the influence of digital marketing, price, and product quality on consumer purchasing decisions of Batik Arkanza in Surakarta. The background shows that digital transformation encourages traditional batik MSMEs to strengthen their online presence while maintaining a balance between price and perceived quality. The objective of this study is to understand the role of digital marketing, price perception, and product quality in shaping consumer purchasing intentions. The study used a descriptive qualitative approach with a naturalistic design, with a population of Batik Arkanza consumers in Surakarta and a purposively selected sample, namely consumers who have purchased Batik Arkanza products through digital channels at least once. The instruments used included in-depth interview guidelines, observations of digital marketing activities, and documentation of Instagram content. Data were analyzed interactively using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results show that effective digital marketing, particularly interactive social media content and live selling, increases product visibility and consumer trust, while competitive prices aligned with perceived quality and product quality consistency significantly encourage consumer purchasing decisions. The research conclusion confirms that Batik Arkanza needs to maintain an integrated strategy of responsive digital engagement, transparent pricing, and consistent product quality standards to maintain consumer loyalty in a digital-based market.